Evaluation of carbon dioxide molding sand for recycling purpose [compact disc] - 241205 Norazma Saari (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006